The Role of Insurance in Driving Economic Growth: Evidence from Nepal - Gwachha, Krishna Prasad; Sayaju, Anjana (Khwopa Journal, 2025)
This study examines the role of insurance in driving economic growth in Nepal. The study analyzed key indicators such as insurance penetration ratio, investment ratio, insurance claim ratio, profitability ratio, and employment trends from 2009/10 to 2023/24. Using an annual aggregate panel dataset from a total of 28 insurance companies —14 life and 14 non-life insurance companies, the study employs the system Generalized Method of Moments (GMM) estimator to address endogeneity and unobserved heterogeneity. The findings reveal that insurance penetration (0.1763, p = 0.0023) significantly boosts economic growth, underscoring its role in risk management and capital mobilization. However, the insurance claim ratio (0.1928, p = 0.1352) shows an insignificant effect, suggesting inefficiencies in claim settlement or low insurance awareness may limit its economic impact. Employment in the sector (0.0347, p = 0.0423) positively influences growth, highlighting job creation and financial benefits. Investments by insurers (0.2258, p = 0.0136) significantly stimulates the economy, emphasizing their role in capital market development. Additionally, insurer profitability (0.0936, p = 0.0202) enhances economic stability, reinforcing the importance of a robust insurance sector. The study concludes that insurance premium collection, investments, employment, and profitability are key drivers of economic growth. Policymakers should prioritize strategies to expand insurance markets, improve claim efficiency, and incentivize investments while fostering labor-intensive growth. The findings support integrated policies that strengthen financial resilience, enhance corporate profitability, and promote job creation. Future research should explore causal mechanisms and sector-specific impacts to refine policies for sustainable development. This study provides critical insights for policymakers, financial institutions, and businesses seeking to harness insurance as a tool for economic transformation in Nepal